The Influence of Entrepreneurial Orientation on Supply Chain Resilience: Evidence from the Small and Medium Sized Enterprises - Munongo, Shallone; Pooe, David (International Journal of Economics and Financial Issues, 2024)
The increasing supply chains disruptions globally often leave many businesses and SMEs vulnerable. The question is whether entrepreneurial orientation of SMEs will make them more resilient to supply chain disruptions. With limited research on the relationship between entrepreneurial orientation and SMEs’ supply chain resilience (SCR) this study seeks to extend our knowledge in that respect. Grounded on the resource-based view and dynamic capabilities theory, this study examined the influence of entrepreneurial orientation on the supply chain resilience of SMEs. Five constructs of entrepreneurial orientation were adapted from literature. A cross-sectional study was employed wherein an online questionnaire was used to collect data from a sample of 173 SMEs owners/or managers. Structural equation modelling (SEM) with partial least square (PLS) technique was used to test the hypothesised model. The overall findings point towards the significant influence of EO on the SCR of SMEs as evidenced by the significant positive effect of innovativeness, risk-taking, pro-activeness and competitive aggressiveness, and autonomy dimensions of entrepreneurial orientation. These results imply that it is critical that SMEs adopt an intentional entrepreneurial oriented management philosophy which can be fostered in several ways including the promotion of a flexible organizational culture that promotes and rewards innovativeness among SME employees, and collaborative efforts between SME owners/managers and policy makers on risk management awareness and competitive aggressiveness literacy and training campaigns.